Bad outcomes, good intentions: approaching the potential misuse of crime data by policy makers - Castro Toledo, Francisco Javier (The crime data handbook, 2024)
Scientific research ethics are challenged today by the risk of misusing research results that could adversely affect or harm both individuals and their environment. In the ethics literature, such risks have been linked to the possibility of research results falling into the wrong hands, that is, for criminal or terrorist purposes. However, crime data misuse can also affect policy makers’ decisions and lead to discrimination, stigmatization, harassment and intimidation of citizens. From a two-fold perspective, this chapter examines the potential misuse of crime data caused by policy decisions: (1) outlining the ethical scope of potential misuses in European security research; and (2) proposing recommendations to minimize this risk based on a ‘Mutual Distrust Model’ between researchers and policy makers.